Epidemiology and Etiology of Prosthetic Stomatitis - Hojimuradov Burkhan Ravshanovich (Scientific Trends, 2024)
Prosthetic stomatitis is a widespread disease in people who use dentures. According to some studies, prosthetic stomatitis affects up to two thirds and even more people using full removable dentures. Despite the frequency of occurrence, prosthetic stomatitis is most often asymptomatic, and only a small proportion of patients experience pain, itching or burning, and the disease is primarily diagnosed during examination as the presence of a focus of inflammation or swelling in the mucous membrane area adjacent to the denture.